Pelaksanaan Bimbingan Dan Konseling Berbasis Nilai-Nilai Budaya Islam Di MTs Negeri Gemolong Kabupaten Sragen - Musthofa, Muhammad; , Dr. Darsinah, M. Si; , Dr. Wafroturrohmah, MM (2015)
Based on the conducted research with the aim of implementing guidance and counseling based on the values of Islamic culture in MTs Gemolong Sragen.This research is classified as descriptive qualitative research. The approach used in conducting this study was a qualitative descriptive approach. In analyzing the data used descriptive qualitative method in a way that inductive thinking of general knowledge and general knowledge starting point.Based on the survey results revealed that the implementation of guidance and counseling in MTs Gemolong Sragen more emphasis on guidance pattern. Guidance and counseling is presented in the form and manner as guidance and counseling in the areas of education, vocational fields, mental health, and in the religious field. The process of guidance and counseling in MTs Gemolong Sragen done by several methods including: methods interviews, group, client-centered methods, educational methods, and methods psycoanalisis with guidance and counseling based values Islamic Culture principeisal hikmah, mauidhoh hasanah dan mujadalah.